Potential biochemical markers of chronic bronchitis and bronchial asthma. Current state of the problem - E. A. Kurtukov; Yu. I. Ragino (Сибирский научный медицинский журнал)
The literature review, according to recent publications, systematizes modern ideas about new biochemical markers of bronchopulmonary pathology, namely chronic obstructive pulmonary disease, chronic bronchitis and bronchial asthma. Information on potential biochemical markers associated with pathology of the bronchopulmonary system is presented: pulmonary activation regulated chemokine (chemokine ligand CCL20), surfactant proteins A and D, pentraxin-3, defensins, alpha-1 antitrypsin, Clara cell protein, interleukin-19, resistin-like molecules. For each biomolecule, its characteristic, biological properties and effects are described, as well as the results of experimental and clinical studies of its effects in bronchopulmonary pathology, the association of elevated blood levels of a biomolecule with clinical manifestations of diseases. It is concluded that today there are a considerable number of new potential biomarkers of the respiratory system diseases for early and effective diagnosis, prevention and treatment of diseases, however, the effects of some of them are either insufficiently studied or contradictory and require further research, which is actively ongoing in the whole world and in Russia.